2018
DOI: 10.3389/fnmol.2018.00409
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Critical Periods for Rapamycin Treatment to Correct Structural Defects in Tsc-1-Suppressed Brain

Abstract: Tuberous sclerosis complex (TSC) is an autosomal dominant neurogenetic disorder affecting the brain and other vital organs. Neurological symptoms include epilepsy, intellectual disability, and autism. TSC is caused by a loss-of-function mutation in the TSC1 or TSC2 gene. These gene products form a protein complex and normally suppress mammalian target of rapamycin (mTOR) activity. mTOR inhibitors have been used to treat subependymal glioma (SEGA) that is a brain tumor characteristic of TSC. However, neuropatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…Interestingly, during neuritogenesis, PTEN is mainly localized in the nucleus and sparsely found in dendrites, but retranslocates into mature dendrites to antagonize mTOR signaling, pause arborization, and promote synaptogenesis (Perandones et al 2004). These data overlap with the narrow time window, in which mTOR inhibitors are able to reverse aberrant outgrowth defects in a tuberous sclerosis complex (Tsc1 f/f ;Gfp-cre) model of autism (Cox et al 2018). Thus, a spatial regulation of PTEN localization is important for proper neuritogenesis, and constant PTEN (nuclear) depletion leads to increased axodendritogenesis with increased synaptogenesis possibly caused by hyperactive mTOR signaling.…”
Section: Neurite Outgrowth and Arborization And Spine Formationmentioning
confidence: 99%
“…Interestingly, during neuritogenesis, PTEN is mainly localized in the nucleus and sparsely found in dendrites, but retranslocates into mature dendrites to antagonize mTOR signaling, pause arborization, and promote synaptogenesis (Perandones et al 2004). These data overlap with the narrow time window, in which mTOR inhibitors are able to reverse aberrant outgrowth defects in a tuberous sclerosis complex (Tsc1 f/f ;Gfp-cre) model of autism (Cox et al 2018). Thus, a spatial regulation of PTEN localization is important for proper neuritogenesis, and constant PTEN (nuclear) depletion leads to increased axodendritogenesis with increased synaptogenesis possibly caused by hyperactive mTOR signaling.…”
Section: Neurite Outgrowth and Arborization And Spine Formationmentioning
confidence: 99%
“…Rapamycin (14 ppm) reduced anxiety-like behavior (thigmotaxis and elevated plus maze) and depressive-like behavior (floating and tail suspension test) in 4-and 12-month-old mice. As shown in Table 5, several studies report that rapamycin reduced behavioral deficits such as anxiety and depression in mouse models of autism [81][82][83][84]. However, Hadamitzky et al [85,86] reported that rapamycin (3 mg/kg, i.p.)…”
Section: Effect Of Rapamycin On Cardiac Function and Disease In Micementioning
confidence: 99%
“…ADPKD accounts for fewer than 2% of TSC cases ( 33 , 34 ). The phenotypic intersection between TSC and ADPKD cases indicate the existence of a functional relationship between the respective genes that have been recently identified as the mTOR signal pathway ( 35 ).…”
Section: Pathophysiologymentioning
confidence: 99%
“…In a large-scale study of 164 pediatric patients with TSC, who underwent serial renal ultrasonography or computed tomography (CT), the authors found that the rate of renal AML increased up to an excess of 50% after the age of five with no renal AMLs in the first year of life ( 65 ). In another longitudinal study involving 60 children, rates of renal AMLs increased from 48% in boys and 60% in girls at a mean age of 6.9 years to 76% in boys and 83% in girls at follow-up at a mean age of 10.5 years ( 33 ). By the time these patients reached adulthood, 33% of the AMLs stopped growing ( 61 ).…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation